Individual and Organizational Well-being when Workplace Conflicts are on the Agenda: A Mixed-methods Study - Enehaug, Heidi; Helmersen, Migle; Mamelund, Svenn-Erik (Nordic Journal of Working Life Studies, 2016)
Previous studies have shown that direct involvement in workplace conflicts may have a significant impact on individual well-being. We used survey and interview data from a large nongovernmental organization (NGO) to analyze both the relationships between direct and indirect involvement in workplace conflicts and individual and organizational well-being. Results show that unaddressed conflicts and nonresponsive or conflict-involved managers are problematic because they fuel already existing conflicts, and also pave the way for new ones. If conflicts are not handled at an early enough stage, they seem to “paralyze” the organization and serve as an interlocking mechanism that contributes to hindering the necessary action from management. In our case, one-fifth of the employees were directly involved in the conflicts, and two-thirds felt that their local working environment had been influenced negatively by the conflicts. The prevalence of mental health problems in the NGO was almost twice as high as in the general Norwegian population, and slightly more than one out of 10 reported reduced work ability. We conclude that individuals directly involved in the conflicts experience negative health consequences, and that this fact, in combination with organizational issues and a very high share of employees indirectly involved in the conflicts, affected the well-being of the whole organization.